Miroir, miroir joli… : l’eau dans le jardin paysage - Ilona Woronow (Projets de Paysage)
The water in the landscape garden focalizes on the stakes and the mechanisms of the artistic inspiration. While the natural watercourse determines the land settlement, its banks artistically disguise the gardener’s contribution. Then comes the visitor. In his presence, the limpidity and the shimmering of the water take part in the spectacle of his solitary promenade. The sole ambiguity that the water casts on the scene is its reflection. Indeed, the texts and pictorial representations of the middle of the eighteenth century show that the mirror’s characteristic, appreciated for its capacity to reproduce the landscape, is systematically ignored when the visitor’s reflection is at stake. In fact, this ignorance seems deliberate, since the assuming of the visitor’s reflection would then make him both an actor and a spectator, and would thus shed some light on the theatrical convention mining the natural of the promenade.